Komunikacja międzykulturowa jako pomost ku integracji społecznej w środowisku wielokulturowym - Bogucka, Katarzyna (Wydawnictwo Naukowe UAM, 2018)
The article focuses on intercultural communication, which creates a passage from a multicultural environment towards social integration and intercultural relations. The author introduces the topic by short characteristics of changes in the modern world, determined by social mobility and multiculturalism. The article presents then some chosen aspects of social integration of migrants seen as bilateral process which requires the development of intercultural competences of both migrants’ and the receiving community. The author further describes intercultural communication and stresses its importance for education and social development. Finally, some factors conditioning the acquisition of intercultural competence with reference to Gordon Allport’s contact hypothesis and informational influences are presented along with highlighting the importance of empathy.
Intercultural Communication as a Bridge Towards Social Integration in a Multicultural Environment
Keywords: migrations; social integration; intercultural communication; intercultural competences